2001
DOI: 10.1088/0305-4470/34/41/320
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization-theoretic analysis of non-equilibrium phase transitions: I. The Becker-Döring equations with power law rate coefficients

Abstract: We study in detail the application of renormalisation theory to models of cluster aggregation and fragmentation of relevance to nucleation and growth processes. We investigate the Becker-Döring equations, originally formulated to describe and analyse non-equilibrium phase transitions, and more recently generalised to describe a wide range of physicochemical problems. In the present paper we analyse how the systematic coarse-graining renormalisation of the Becker-Döring system of equations affects the aggregati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…A similar result has also been obtained by using generating functions and scaling ansatzs [15]. In summary, the previous results have pointed out three growth regimes for α ≤ 1 (for α > 1 normalizable solutions are not found), depending on the exponents of the reaction rates [15][16][17]. In the asymmetric case α > µ detachment dominates, and very slow or stagnated growth is expected.…”
Section: The Model Of Growthsupporting
confidence: 79%
See 2 more Smart Citations
“…A similar result has also been obtained by using generating functions and scaling ansatzs [15]. In summary, the previous results have pointed out three growth regimes for α ≤ 1 (for α > 1 normalizable solutions are not found), depending on the exponents of the reaction rates [15][16][17]. In the asymmetric case α > µ detachment dominates, and very slow or stagnated growth is expected.…”
Section: The Model Of Growthsupporting
confidence: 79%
“…Equations similar to REs Eqs. (1)-(2) have been studied previously by using asymptotic matched expansion and large-time asymptotic expansions [16], as well as by using renormalization methods [17]. In both cases, three classes of growth are found: aggregation-dominated and detachment-dominated cases, and the case where aggregation and detachment are exactly balanced.…”
Section: The Model Of Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Case VI: η < γ < 0 In this case the system evolves to the steady-state solution (3.6), which for large aggregation numbers r has the asymptotic behaviour c sss r ∼ (J/ac 1 )e −γr and is thus divergent (since γ < 0). At large times the kinetics can be determined by considering ψ(r, t) = c r (t)/c sss r which satisfies ∂ψ ∂t = and the transformations χ = y/t and ψ = g(χ) yield 25) and hence…”
Section: Case Iv(c)mentioning
confidence: 99%
“…Results for the case of rates which depend on size in a power-law fashion (a case of direct relevance to classical nucleation theory) have been derived by King & Wattis [13,26]. Coveney, Wattis and Bolton have shown that by eliminating a proportion of the concentration variables, a coarse-grained mesoscopic description can be obtained [10,24,25,6]. The resulting model also has the form of a Becker-Döring system, with modified aggregation and fragmentation rate coefficients; the coarse-graining procedure can be reapplied and thus has the form of a renormalisation transformation, with each application filtering out more of the detailed dynamics of the cluster size distribution.…”
Section: Introductionmentioning
confidence: 99%